Marshall cavendish cambridge primary maths pupil's book 2 - Soh, Christina; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
The "Maths 2, Pupil's Book" builds on the concepts introduced in Maths 1, advancing to more complex operations such as multiplication and division, as well as introducing fractions and basic geometry. It features a variety of problems and visual aids to enhance understanding and encourage critical thinking.